Agricultural UAV Path Planning Based on Improved A* and Gravity Search Mixed Algorithm. (September 2020) - Tian, Ru; Cao, Maoyong; Ma, Fengying; Ji, Peng
Abstract: In order to ensure the accuracy, efficiency and energy saving of Unmanned Aerial Vehicles (UAVs) in irregular working areas, this paper has carried out research on its path planning methods. Taking the heading angle and return point of agricultural UAVs as the optimization objectives, the plan was made by improving the A* and gravitational search algorithm to plan the optimal path. First, the execution process of the algorithm is analysed, the application model is solved, and then the simulation experiment is performed through MATLAB. The path calculated by the proposed method was also compared with the unplanned and gravitational search algorithm planned path respectively, which showed the non-spraying distance of the proposed method was reduced by 23.18% and 5.83%, while the excess coverage of pesticide spraying was reduced by 64.47% and 64.47%. The study indicated that the proposed method which could produce paths with less working time was a reasonable, feasible and useful solution for the path planning problem of the plant protection UAV.